Biliary Drainage Before and After Liver Resection for Perihilar Cholangiocarcinoma. Issue 6 (June 2020) - Enomoto, Laura M.; Dixon, Matthew E. B.; Burdette, Allene; Gusani, Niraj J.
Perihilar cholangiocarcinoma (PHC) is a rare tumor that requires surgical resection for a potential cure. The role of preoperative biliary drainage has long been debated, given its treatment of biliary sepsis and decompression of the future liver remnant (FLR), but high procedure-specific morbidity. The indications, methods, and outcomes for preoperative biliary drainage are discussed to serve as a guide for perioperative management of patients with resectable PHC. Multiple studies from the literature related to perihilar cholangiocarcinoma, biliary drainage, and management of the FLR were reviewed. Commonly employed preoperative biliary drainage includes endoscopic biliary stenting and percutaneous transhepatic biliary drainage. Drainage of the FLR remains controversial, with most experts recommending drainage of the only in patients with an FLR <50%. Biliary drainage for resectable PHC requires a patient-specific approach with careful determination of the FLR and balancing of potential morbidity with the benefits of drainage.